Common Ground in Demonstrative Reference: The Case of Mano (Mande) - Khachaturyan, Maria (Frontiers in Psychology, 2020)
That demonstratives often have endophoric functions marking referents outside the physical space of interaction but accessible through cognition, especially memory, is well-known. These functions are often classified as independent from exophoric ones and are typically seen as secondary with respect to spatial deixis. However, data from multiple languages show that cognitive access to referents functions alongside of perceptual access, including vision. Cognitive access is enabled by prior interactions and prior familiarity with the referents. As a result of such interactions, the interlocutors share a great deal of knowledge about the referents, which facilitates reference to objects in the interactive field. The centrality of common ground in reference to an object at the interactive scene challenges the often assumed classification of demonstrative reference into exophoric and endophoric. I illustrate this idea throughout the paper by using first-hand data from Mano, a Mande language of Guinea. Adding another argument in favor of viewing demonstrative reference as a social, interactive process, the Mano data push the idea of salience of non-spatial parameters further and emphasizes the importance of short and long-term interactional history and cultural knowledge both for the choice of demonstratives in exophoric reference and for the structuring of the demonstrative paradigm.